Correlation of the intronic LOXL1 polymorphism rs11638944 with pseudoexfoliation syndrome and glaucoma in a Greek population - Papadopoulou,M.K.; Chatziralli, I; Tzika,K.; Chiras,D.; Kitsos,G.; Kroupis, C. (Ophthalmic Genet., 2021)
BACKGROUND: The purpose of this study is the development and validation of a novel and robust genotyping method for a new lysyl oxidase-like 1 (LOXL1) intronic polymorphism (rs11638944, C > G) and the investigation of its potential association with pseudoexfoliation syndrome (PXS) and pseudoexfoliation glaucoma (PXG) in a Greek population. MATERIAL AND METHODS: 242 DNA samples from 49 PXS, 64 PXG, 50 primary open-angle glaucoma (POAG) patients and 79 healthy age-matched controls were analyzed. Novel methodologies were developed and optimized, in order to genotype the intronic LOXL1 polymorphism: a) a real-time qPCR and melting curve analysis in the Light Cycler platform for rapid and cost-effective analysis and, b) a conventional PCR-RFLP method for analysis of a small number of samples. In selected samples, validity was checked with the reference DNA Sequencing method. RESULTS: The real-time qPCR methodology was reliable, demonstrating good efficiency, reproducibility, accuracy in genotyping (100% concordance with the PCR-RFLP method and DNA Sequencing), with good allele discrimination (Tm = 53.26 degrees C for C allele, Tm = 61.83 degrees C for G allele, DeltaTm = 8.57 degrees C). The results were characterized by Hardy-Weinberg equilibrium in all groups. An increase from 18% in healthy controls to 61% in PXS patients was detected for the G/G homozygote thus, the C allele is protective for PXS with OR = 0.22 (95%CI: 0.11-0.42, p < .0001). Moreover, an increase from 18% in healthy controls to 70% in PXG patients was detected for the G/G homozygote thus, the C allele is protective for PXG with OR = 0.13 (95%CI: 0.06-0.25, p < .0001). CONCLUSIONS: A statistically significant association was verified for the intronic LOXL1 polymorphism rs11638944 and PXS/PXG in a Greek population
IS - 1744-5094 (Electronic) IS - 1381-6810 (Linking) LA - eng PT - Journal Article RN - EC 1.4.- (Amino Acid Oxidoreductases) RN - EC 1.4.3.- (LOXL1 protein, human) SB - IM
Keywords: Aged; Aged,80 and over; Amino Acid Oxidoreductases; Epidemiology; Exfoliation Syndrome; Female; genetics; Genotyping Techniques; Glaucoma,Open-Angle; Greece; Humans; Intraocular Pressure; Introns; Male; Middle Aged; physiology; physiopathology; Polymorphism,Restriction Fragment Length; Polymorphism,Single Nucleotide; Real-Time Polymerase Chain Reaction; Slit Lamp Microscopy; Tonometry,Ocular; Visual Acuity